Literary Analysis of Mary’s Lineage: Unraveling the Controversy in Quranic and Biblical Texts within the Context of Literary Studies - Sudinpreeda, Hakim (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2024)
The controversy over Mary being termed the “sister of Aaron” in the Quran prompts a critical examination of its impact on the Quranic narrative. This study explores historical, literary, and cultural contexts, utilizing intertextuality in the Quranic and Christian traditions. Employing a methodology involving a thorough analysis of Biblical and Quranic texts, along with relevant secondary literature, we scrutinize language styles, genre specifications, and cultural contexts. The investigation reveals diverse perspectives on Mary’s lineage. In alignment with some mainstream Islamic interpretations, the paper posits that the Quran’s reference to Mary as Aaron’s sister is symbolic, not a literal biological relationship. This interpretation is supported by the distinctive portrayal of Aaron in the Quran and the Bible, emphasizing Mary’s unique role. Additionally, the paper draws evidence from accepted religious sources in Jewish and Christian traditions, reinforcing the Quranic term “Mary, sister of Aaron.” In conclusion, the study advocates for a nuanced understanding, asserting that interpreting the Quran’s symbolic connections does not undermine its authenticity. Instead, it aligns with a broader tradition of symbolism and intertextuality in religious texts, reinforcing the Quran’s distinct portrayal.